Athen, Griechenland. Werkstätten am Südrand der Kerameikosstraße: Töpferwerkstätten und eine Ölmühle des 5. Jahrhunderts v. Chr. Die Arbeiten des Jahres 2020 - Stroszeck, Jutta; Lehmann, Franziska (e-Forschungsberichte des DAI, 2020)
Due to the known restrictions for 2020, the Kerameikos team this year, during a short campaign, cleaned and documented workshop structures on the south western side of the Kerameikos street. The area had already been excavated and published in the early 1940s by Kurt Gebauer. The remnants of a large water basin were cleared and documented. It probably belonged to a potter’s workshop that existed there after the 1st century BC during the Roman period. Apart from that, a large structure was cleaned and re-investigated whose first interpretation as a fountain seemed problematic. Cleaning and re-documenting the structure, that can be dated to the 5th century BC, made it obvious that in fact, the structure is an ancient classical olive press.